Gerakan Protes Masyarakat Kampung Partikelir di Kota Surabaya, 1910-1916 - Syafiqurrahman, Abdul Aziz; Sutiyah, Sutiyah; Djono, Djono (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
This study aims to explain the things that gave rise to the protest movement, the form, and the results of the protest movement of the private village community in Surabaya City in 1910-1916. This study uses a historical method that has four steps, consisting of heuristics, source criticism, interpretation, and historiography. The results of the study can be concluded that the general cause that gave rise to the protest movement was the uncertainty of land ownership status in the private village. Changes in the work system to non-agricultural which made it difficult for the community due to limited skills and education. Eviction of housing caused the Bumiputra community to lose their right to live. The specific cause of the protest movement was the eviction and poverty conditions in the Keputran Lor village which caused feelings of anxiety. The form of protest movement of private village communities in Surabaya was carried out by illegally occupying private land and carrying out various strikes against the fulfillment of obligations. The result of the protest movement of private village was the emergence of slums and poor settlements on government-owned land. awareness of law and national politics. Resistance to village politics which are regulated arbitrarily.